Stress Testing of Steel Suspender of Arch Bridge Model Based on Induced Magnetic Flux Method - Guangyuan Weng; Liu Yang; Zhu Xiyu (Advances in Materials Science and Engineering)
To establish an online nondestructive stress testing method for arch bridge suspender based on the principle of magnetic coupling, the magnetic mechanical property of Q345qD steel is explored taking an arch bridge model structure with Q345qD steel suspender as the research object. Under the action of magnetic field excited by a coil, the test of the coupling relationship between stress and excitation flux is carried out. The theoretical model of stress-magnetic flux is simplified to better meet the requirements of engineering applications. The excitation device, magnetic flux measurement device, stress-magnetic flux data analysis program, and so on are developed, and the magnetic coupling stress detection system is integrated. The test model structure of a steel arch bridge with suspenders of Q345qD alloy steel is designed and made; under the different load conditions, the stresses of the suspenders are tested and studied. The relationships between induced magnetic flux and technical magnetized voltage, test load of model structure, and different stress conditions of the suspenders are analyzed; with the induction magnetic flux as the parameter, the stress-magnetic flux coupling model is established. The test results based on the stress-magnetic flux coupling model are compared with those of the traditional stress-strain test in a linear elastic range; it shows that the two testing methods are in good agreement with each other, and the maximum error is less than 5%. Meanwhile, with the increase in the load on the suspender, the tension stress increases and the induced magnetic flux decreases, showing a good linear relationship. The conclusions drawn from the research can provide important reference for health monitoring of suspenders of arch bridges.